DAMPAK BRAND EQUITY PADA KEPUTUSAN PEMBELIAN MELALUI BRAND PREFERENCE KONSUMEN PADA PRODUK TELEVISI MEREK SONY DI KOTA PEKANBARU - Soracca Devi Prajnagaja; Lilis Sulistyowati; Sri Restuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of brand equity on the purchase decisions of consumers through brand preference Sony brand televisions in the city of Pekanbaru. This study used 112 samples. The analytical method used is descriptive analysis method is a way to test variables, regression test, and final test path analysis or path analysis. From the results of the testing that has been done, brand equity directly affect Consumer Buying Decision on Sony Television Products in Pekanbaru "is acceptable because the value of the regression is positive and t count> t table. Influential Brand Equity Against Indirect Consumer Purchase Decision Through Brand Preference on Sony Television Products in Pekanbaru "received as a result of the indirect effect of variables consisting of Brand Equity (Brand Awareness, Brand Association, Perceived Quality) on consumer purchasing decisions through more Brand Preference greater than the value of the direct influence of the variables consisting of Brand Equity (Brand Awareness, Brand Association, Perceived Quality) on consumer purchasing decisions through Brand Preference. So when variables consisting of Brand Equity (Brand Awareness, Brand Association, Perceived Quality) increased, it will cause an increase in the variable purchase decision and also the variable Brand Preference.Keywords: Brand Equity, Brand Preference, Purchase Decision